Bilingual Education System at Primary Schools of Pakistan - Raja, Farhan Uddin (Journal of Research in Humanities, 2023)
A nation’s growth rests upon multiple factors but among those the most vital asset is its educated people serving and contributing towards its development and prosperity. It implies that education is the key factor in the growth of any nation, and in a multilingual and multicultural society like Pakistan, it becomes imperative that the medium of instruction in education system needs to be addressed. This research article aims to explore if a system of bilingual education at primary schools of Pakistan can be proposed, in which the basic knowledge and information will be provided to the students in their native language at primary level. It also aims to investigate if a bilingual education system can successfully be implemented and run in a society like Pakistan which is linguistically well diverse. The rationale of this research article stems from the need that the teaching of basic concepts in different subjects and provision of knowledge in the native language to the students at primary schools lead to increased cognitive development (Bloom’s Taxonomy) and self confidence. It lies within the paradigms of Qualitative research and the results are reflected through the analysis of the questions put forward by Tucker, G. Richard (1999) regarding the prospects of bilingual or multilingual education system in multilingual societies, and recommendations made by Luis Enrique López (1999) for the successful implementation process of a bilingual education system.